Answer:
a = - 4, b = 5
Step-by-step explanation:
Expand the left side and compare the coefficients of like terms on the right side.
- 3(2x² + ax + b)
= - 6x² - 3ax - 3b
Comparing like terms with - 6x² + 12x - 15
x - term → - 3a = 12 ( divide both sides by - 3 )
a = - 4
constant term → - 3b = - 15 ( divide both sides by - 3 )
b = 5
Answer:
39°
Step-by-step explanation:
51° +? = 90°
? = 90° - 51°
? = 39°
Hope it helps you in your learning process.
You would multiply the power by the powers of both exponents
2 × 3 = 6 so a^6
3 × 4 = 12 so b^12
Answer is
a^6b^12
Answer:
B I think
Step-by-step explanation: